Sistem Pembacaan kWh Meter Digital berbasis Raspberry Pi - Thomas Kalsanta; Andreas Handojo; Resmana Lim (Jurnal Infra, 2019)
Electricity nowadays has become a fundamental necessity for various human activities for various functions. In Indonesia authorized as a provider of electrical energy is Negera Electricity Company (PLN), to know the large electrical energy used, a tool is needed called kWh meters. There are two kinds of analog kWh meters and digital kWh meters. The recording carried out by PLN is now varied from the coming of the officers to record manually or by doing many prepaid systems. This kind of recording is a waste of time and is less effective to do in modern times like this that everything is instant.Things like this will certainly begin to be abandoned when not updated soon. It is therefore necessary to centrally read digital kWh Meter technology that can be accessed anywhere and anytime. Looking at the above problem, it takes an application to see the use of kWh, voltage, current, power, and power factor. To monitor the use of a tenant tenant centrally and anywhere can be accessed.This system uses Raspberry Pi and Website. This system can detect the use of kWh meters now with digital kWh meters connected with Raspberry Pi and the user or admin can see the usage of the website in direct. Users can view graphs of the usage of kWh, voltage, current, power, and power factor. In addition, users can also get notifications if they exceed the specified limit. This system can help record kWh on each tenant as an effective way